Health Reform during the 21st Century: Dispute of Knowledge and Planned Ignorance in the Era of Digital Acceleration and Collapse of Bioethics - Breilh Paz y Miño, Jaime Eduardo (2023)
The greatest paradox of human society during the 21st century is the vertiginous acceleration of a runaway neo-extractivism and the collapse of principles and values that enable healthy good living. This is aggravated in current times, paradoxically, when humanity reaches the highest thresholds of knowledge and technology. The exponential and parallel growth of the private accumulation of wealth, together with the reproduction of a profound inequality, now take place even in unprecedented settings and dimensions of hyper-neoliberal accumulation, within a civilization guided by greed. Consequences on the planetary health field are devastating. In this era, human knowledge and accelerated digital thinking—misnamed “artificial intelligence”—, rather than strongly promoting the emancipatory uses of technologies, these are generating increasingly dangerous production systems, distorting the potential of science and distancing universities from a fight for so-called “epistemic justice”, in the complex task of overcoming biased scientific knowledge that feeds strategic ignorance and blocks academic reform. ----------Keywords: university health training, hyperneoliberalism, strategic ignorance, epistemic justice, neoextractivism, digital thinking (“artificial intelligence”), health reform.